2021
DOI: 10.3847/2041-8213/ac1e2d
|View full text |Cite
|
Sign up to set email alerts
|

On the Detection of Exomoons Transiting Isolated Planetary-mass Objects

Abstract: All-sky imaging surveys have identified several dozen isolated planetary-mass objects (IPMOs) far away from any star. Here we examine the prospects for detecting transiting moons around these objects. We expect transiting moons to be common, occurring around 10%-15% of IPMOs, given that close-orbiting moons have a high geometric transit probability and are expected to be a common outcome of giant planet formation. The IPMOs offer an advantage over other directly imaged planets in that high-contrast imaging is … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 150 publications
0
19
0
Order By: Relevance
“…2MASS J0835+1953 b joins 2MASS J1119-1137 AB b (Limbach et al 2021) as the only reported planet candidates around brown dwarfs, to date. We intend to continue our follow-up campaign of 2MASS J0835+1953, but the effectiveness of this effort will be limited by the typical constraints of ground-based observing, namely weather losses and gaps during the day.…”
Section: Discussionmentioning
confidence: 81%
“…2MASS J0835+1953 b joins 2MASS J1119-1137 AB b (Limbach et al 2021) as the only reported planet candidates around brown dwarfs, to date. We intend to continue our follow-up campaign of 2MASS J0835+1953, but the effectiveness of this effort will be limited by the typical constraints of ground-based observing, namely weather losses and gaps during the day.…”
Section: Discussionmentioning
confidence: 81%
“…During those two rotations we see significant evolution in the light curve, including the emergence of a ∼ 1% dip with a 1 hr duration in the light curve at 15 hr. This dip may be due to the emergence of a Great Red Spot analog (Apai et al 2017), or even a transiting satellite (Tamburo & Muir-head 2019;Limbach et al 2021). Long-term follow-up observations could differentiate the cause of such dips in the light curve of 2MASS J0642+4101.…”
Section: Youth and Variability Properties Of Inidividual Objectsmentioning
confidence: 99%
“…Photometric observations of isolated planetary mass objects (Limbach et al 2021) would represent a useful pathway to understand their intrinsic variability and to demonstrate the presence of satellites around these objects. The comparison of the frequency of exomoons around isolated planetary-mass objects with those around planetary companions orbiting stars would also be highly interesting for our understanding of their formation mechanisms.…”
Section: Transitsmentioning
confidence: 99%